ANALISIS MODEL MATEMATIKA PERTUKARAN PANAS PADA FLUIDA DI HEAT EXCHANGER TIPE SHELL AND TUBE YANG DIGUNAKAN DI PT. PUPUK KALTIM TBK. - Qoriatul, Q; Fatahillah, Arif; Dafik, D; Sri Lestari, Nurcholif Diah (Department of Mathematics Education , University of Jember, 2013)
Abstract. Materials to produce fertilizer are NH3 Liquid and CO2 gas. Required CO2 gas should be free from condensation, so CO2 gas is refrigerated in intercooler. In this research, we analyse of mathematic model for heat transfer in fluid with finite volume method. We will review how the CO2 gas cooling process from mathematics model point of view. We will model the equations for CO2 gas cooling process which includes momentum dan energy. After that this model will be discretizatied. For numerical solution, we will use Matlab and Fluent to simulate CO2 gas cooling process. The simulation result using Matlab and Fluent forms will be presented descriptively in charts, tables, and images to show how the distribution process of heat transfer. The result show for error is 0,0087. In conclusion the model accurate for solving heat transfer process in CO2 gas. Key Words : Mathematics Models, Heat transfer, Finite Volume Methode,